Control of Toxin-Antitoxin Systems by Proteases in Mycobacterium Tuberculosis - Bordes, Patricia (Frontiers Media S.A., 2021)

(untitled) (Front Mol Biosci)
Toxin-antitoxin (TA) systems are small genetic elements composed of a noxious toxin and a counteracting cognate antitoxin. Although they are widespread in bacterial chromosomes and in mobile genetic elements, their cellular functions and activation mechanisms remain largely unknown. It has been proposed that toxin activation or expression of the TA operon could rely on the degradation of generally less stable antitoxins by cellular proteases. The resulting active toxin would then target essential cellular processes and inhibit bacterial growth. Although interplay between proteases and TA systems has been observed, evidences for such activation cycle are very limited. Herein, we present an overview of the current knowledge on TA recognition by proteases with a main focus on the major human pathogen Mycobacterium tuberculosis, which harbours multiple TA systems (over 80), the essential AAA + stress proteases, ClpC1P1P2 and ClpXP1P2, and the Pup-proteasome system.